2021
DOI: 10.3748/wjg.v27.i41.7065
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in a population highly affected by obesity and type 2 diabetes and susceptibility to COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) is a disease produced by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and it is currently causing a catastrophic pandemic affecting humans worldwide. This disease has been lethal for approximately 3.12 million people around the world since January 2020. Globally, among the most affected countries, Mexico ranks third in deaths after the United States of America and Brazil. Although the high number of deceased people might also be explained by social aspects an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 118 publications
1
6
0
Order By: Relevance
“…Coinfection with this bacterium was linked with deterioration of overall health, especially in ICU COVID-19 patients [ 42 ]. K. pneumoniae has been reported to be the most commonly isolated bacteria from COVID-19 patients (19.4%) [ 43 ], and the current investigation showed higher prevalence of K. pneumoniae in non-ICU compared to ICU patients. Isolated strains of K. pneumoniae from blood and urine of ICU patients had complete resistance profiles; however, isolates from sputum samples for the same group presented with no resistance and 62% resistance to colistin and amikacin, respectively.…”
Section: Discussionsupporting
confidence: 51%
“…Coinfection with this bacterium was linked with deterioration of overall health, especially in ICU COVID-19 patients [ 42 ]. K. pneumoniae has been reported to be the most commonly isolated bacteria from COVID-19 patients (19.4%) [ 43 ], and the current investigation showed higher prevalence of K. pneumoniae in non-ICU compared to ICU patients. Isolated strains of K. pneumoniae from blood and urine of ICU patients had complete resistance profiles; however, isolates from sputum samples for the same group presented with no resistance and 62% resistance to colistin and amikacin, respectively.…”
Section: Discussionsupporting
confidence: 51%
“…Additionally, obesity is a risk factor for children with asthma that are infected with SARS-CoV-2, because it is associated with the dysfunction of their small airways [99]. These factors are problematic as there are children that have adopted less healthy lifestyles due to the pandemic and accelerated their weight gain [100,101]. Furthermore, comorbidities such as obesity, type 2 diabetes, and high blood pressure have been associated with imbalances in the gut microbiota that can result in inflammatory dysfunctions that worsen COVID-19 symptoms [102].…”
Section: Covid-19 Comorbidities Associated With Dysbiosis Imbalances ...mentioning
confidence: 99%
“…The prebiotic and probiotic cohorts saw reduced instances of virus-associated respiratory tract infections (p < 0.001 and p = 0.022, respectively). A study administering Lab4P probiotic to overweight and obese adults (n = 220) daily suggested that probiotics may reduce upper respiratory tract infection symptoms and stabilize gut microbiota diversity, which may be particularly relevant in COVID-19 infections, in which obesity is associated with worse outcomes [101,190].…”
Section: Probiotics and Other Microbial Therapeutics In Covid-19mentioning
confidence: 99%
“…Indeed, obesity-related gastrointestinal microbiota dysbiosis, in concert with increased gut permeability ( 145 ), contributes to inflammation by promoting systemic endotoxemia which is the direct consequence of the leak of lipopolysaccharides (LPS) through the dysfunctional gut barrier ( 146 ). Ultimately, this inflammatory status, fueled by gut microbiota dysbiosis, amplifies the so-called “cytokine storm,” thereby predisposing subjects with obesity to more severe COVID-19 symptoms and increased risk of death ( 147 ).…”
Section: Microbiome and Covid-19mentioning
confidence: 99%